2016
DOI: 10.1007/s10461-016-1519-2
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and Behavioral Characteristics of High-Risk Men Who Have Sex with Men (MSM) of Unknown HIV Positive Serostatus in Bangkok, Thailand

Abstract: HIV prevalence remains high in men who have sex with men (MSM) in Bangkok. Even though resources for HIV testing and treatment are available for all, a large proportion of MSM still do not get HIV tested. We studied high risk MSM who are unaware of their HIV status to help maximize effectiveness of our resources. Convenience sampling was conducted among MSM who came for HIV testing at the Thai Red Cross Anonymous Clinic and two popular drop-in centers in Bangkok. Inclusion criteria were MSM aged >18 years, hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 18 publications
4
19
0
1
Order By: Relevance
“…We found that roughly half of MSM in our sample had ever tested for HIV in their lifetime. This figure is similar to MSM data from China, higher than those from Thailand [38], and lower than those from Cambodia [39], South Africa [40], Peru [41], Australia [42], and the US [43]. We also found that only 23% of men tested for HIV at least once every six months, which is much lower than recommendations by US CDC guidelines [36].…”
Section: Discussionsupporting
confidence: 84%
“…We found that roughly half of MSM in our sample had ever tested for HIV in their lifetime. This figure is similar to MSM data from China, higher than those from Thailand [38], and lower than those from Cambodia [39], South Africa [40], Peru [41], Australia [42], and the US [43]. We also found that only 23% of men tested for HIV at least once every six months, which is much lower than recommendations by US CDC guidelines [36].…”
Section: Discussionsupporting
confidence: 84%
“…A sizeable portion of HIV-infected persons (~ 15%) are unaware of their HIV serostatus in the US and Spain [1,2]. Men who have sex with men and persons who inject drugs are at greater risk for unknown HIV serostatus [1], which is associated with high-risk behaviors in Latinos and other ethnic groups [3][4][5]. Undetected HIV infection undermines HIV prevention and treatment goals to curb the epidemic and improve treatment outcomes [6].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the prevalence of HIV testing among MSM remained low with 32.6% of participants having been tested for HIV in the last 3 months and 62.5% of participants having been tested for HIV in their lifetime. These testing proportions are higher than those from Thailand in 2014 [ 25 ] and Zhejiang, China in 2014 [ 1 ], but lower than those from Cambodia in 2015 [ 26 ]. The HIV testing proportion is still far behind the UNAIDS target for 90% testing among infected individuals in 2014 [ 27 ].…”
Section: Discussionmentioning
confidence: 99%